2013
DOI: 10.7120/09627286.22.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal pattern of salivary cortisol secretion in the greater one-horned rhino(Rhinoceros unicornis)

Abstract: The Indian rhinoceros or greater one-horned rhino (Rhinoceros unicornis) is listed as vulnerable by the IUCN Red List of Threatened Species and, therefore, captive individuals have been subject to the European Endangered Species Programme since 1990. Enhancement of welfare is key in ensuring the breeding success of this species in captivity. Salivary cortisol has been recently used to assess welfare of captive and free-ranging animals. Nevertheless, rhythms of cortisol secretion may fluctuate throughout the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
3
0
2
Order By: Relevance
“…In this study, the number of animals is relatively low, which limits the significance of the results. Since it is a remarkable fact that it is very difficult to find large numbers of a wild species with the behavioral and housing requirements of the white rhinoceroses sharing the same enclosure, many previous studies involving wild species have used a low number of subjects and produced meaningful and insightful findings [ 41 , 42 , 43 , 44 ]. A common practice is that, to increase the number of individuals in a study of wild animals, data from animals housed in different institutions are used [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the number of animals is relatively low, which limits the significance of the results. Since it is a remarkable fact that it is very difficult to find large numbers of a wild species with the behavioral and housing requirements of the white rhinoceroses sharing the same enclosure, many previous studies involving wild species have used a low number of subjects and produced meaningful and insightful findings [ 41 , 42 , 43 , 44 ]. A common practice is that, to increase the number of individuals in a study of wild animals, data from animals housed in different institutions are used [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is some controversy as to whether cortisol follows a seasonal pattern. It has been previously reported that cortisol secretion follows a seasonal pattern in captive Indian rhinos ( Rhinoceros unicornis ) [ 41 ]. However, our results reveal a minimally elevated mean fGCM value in summer samples compared to that of winter samples (not statistically significant); furthermore, the fluctuations in the values between summer and winter were different among the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Para la medición de los metabolitos de glucocorticoides se tuvieron en cuenta las fluctuaciones en los niveles relativos de cortisol para cada individuo (24,25,26,27). Para este caso, se observó un comportamiento similar de los resultados en ambos ejemplares para el caso de Luna; para la primera semana de enriquecimiento los valores permanecieron muy similares a los de la primera semana sin enriquecimiento, mientras que para la segunda semana de enriquecimiento estos aumentaron de 16 ng/ml (sin enriquecimiento) a 661 ng/ml.…”
Section: Discussionunclassified
“…El flujo de visitantes también pudo contribuir a aumentar los niveles de estrés; debido a la naturaleza solitaria y salvaje de estos individuos, es posible afirmar que la proximidad con los seres humanos es un factor de estrés, ya que estos no se encuentran habituados a interactuar con ellos (24,25,26).…”
Section: Discussionunclassified
“…Several studies have developed non-invasive techniques (which limit animal disturbance) to determine the hormonal profiles in order to monitor and improve the management of different animal populations, especially in endangered species [ 7 , 11 , 14 , 15 , 16 , 17 ]. In the rhinoceros, the biological samples used to perform non-invasive hormone assays are feces, urine, and saliva [ 16 , 18 , 19 ]; however, when it comes to wild populations, fecal samples are extensively employed and highly convenient, particularly due to their ease of collection and preservation. Fecal-excreted metabolites are vulnerable to bacterial and environmental degradation, but as long as feces is collected relatively soon after defecation, the metabolites present are a reliable indicator of the physiological state [ 20 ].…”
Section: Introductionmentioning
confidence: 99%